2009
DOI: 10.1002/cncy.20019
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory second opinion in cytopathology

Abstract: BACKGROUND:Mandatory review of outside pathologic material is intended to detect interpretive errors that may have a clinically significant impact on patient care. Prior to definitive treatment of referred patients, the University of Iowa Carver College of Medicine requires a review of pertinent pathologic material previously obtained at outside institutions. The aims of this study were to determine if this local standard of practice has a measurable impact on patient care.METHODS:The pathologic diagnoses of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
(28 reference statements)
1
30
1
Order By: Relevance
“…Second opinions solely on lung cancer have never been investigated and in other reports with mixed/miscellaneous patient populations, the number of lung cancer cases was too limited to draw specific conclusions in this group (Maaskant et al, 2009;Lueck et al, 2009;Manion et al, 2008;Mellink et al, 1999;Tsung, 2004). Although it is difficult to compare present results with general second opinion data, it is striking that our percentages discrepancies and their potential impact on patient outcomes are higher than reported in literature.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Second opinions solely on lung cancer have never been investigated and in other reports with mixed/miscellaneous patient populations, the number of lung cancer cases was too limited to draw specific conclusions in this group (Maaskant et al, 2009;Lueck et al, 2009;Manion et al, 2008;Mellink et al, 1999;Tsung, 2004). Although it is difficult to compare present results with general second opinion data, it is striking that our percentages discrepancies and their potential impact on patient outcomes are higher than reported in literature.…”
Section: Discussioncontrasting
confidence: 53%
“…Second opinions have proven to be of value for a number of different diseases, especially in oncology (Briggs, Flynn, Worthington, Rennie, & McKinstry, 2008;Kronz, Westra, & Epstein, 1999;Lueck, Jensen, Cohen, & Weydert, 2009;Manion, Cohen, & Weydert, 2008). The percentages of discrepancies after a second opinion vary between 1% and 60%, depending on the disease and anatomic site, the nature and quality of pathological specimen (cytology or histopathology), the applied definition criteria for the changes (in diagnosis, stage or therapeutic advice), their clinical impact on therapy and/or prognosis and the patient population (Tattersall et al, 2009;Briggs et al, 2008;Kronz et al, 1999;Lueck et al, 2009;Manion et al, 2008;Frable, 2006;Kronz & Westra, 2005;Zembowicz, Ahmad, & Lyle, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Jing et al [5], for instance, reported that intradepartmental consensus review of 50 thyroid aspirates previously classified as AUS/FLUS resulted in a definitive diagnosis in 74% of the cases with a consequent improvement of diagnostic accuracy. Indeed, examination of pathological material, including cytological specimens, is an accepted practice in many institutions, especially in the context of a second opinion for referred patients before clinical management [6,7,8,9,10,11]. In a large series of institutional consultations for 3,885 thyroid FNAs, Olson et al [12] showed that the second review significantly decreased the rate of indeterminate cytological diagnosis with an increase in numbers of nondiagnostic (unsatisfactory), benign and malignant diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…The term "second opinion" has been widely reported also in histology [10,11] and pathology (e.g. thyroid pathology) [12][13][14][15][16][17][18][19][20] where the diagnosis is often difficult, misunderstood and strongly based on the healthcare professionals' experience.…”
Section: Introductionmentioning
confidence: 99%
“…However, the internet sites are often lacking of adequate information concerning disease complications and aftercare [4]. This web-searching behaviour is often continuous, compulsory, somehow obsessive, leading to the "Web Babel Syndrome", defined as a physician-patient communication gap frequently occurring when the patient affected by multiple synchronous pathologies, feeds back heterogeneous and misleading informations and prescriptions with the risk to drop in a confusionary state [5][6][7][8].In 1999, the Institute of Medicine report cited fatal medical errors in some 40,000-98,000 Americans PER year [8] supporting once more the concept that a further consultation or specialistic second opinion may be useful antidote to lethal misdiagnosis [9].The term "second opinion" has been widely reported also in histology [10,11] and pathology (e.g. thyroid pathology) [12][13][14][15][16][17][18][19][20] where the diagnosis is often difficult, misunderstood and strongly based on the healthcare professionals' experience.…”
mentioning
confidence: 99%